Enabling Conditions for Second Pillars of Pension Systems - Rudolph, Heinz; Rocha, Roberto (2012)
This note adds to the existing literature by examining the enabling conditions for the creation of mandatory funded pension funds, and identifying additional factors that are important to consider in the early stages of the reform. The note stresses the importance of some factors that had already been identified in previous literature but not fully observed by reforming countries, including the strong and lasting commitment of the authorities with the reform, the fiscal commitment with the reform, and some basic financial infrastructure. The analysis is also extended to analyze the role of supervision in the early stages of the reform and the role of the government in fostering the development of the domestic capital market.